The Influence of the Annales School and Colonial Historiography in Indonesian Islamic Historiography - Ali, M. Nasihudin; Lestari, Rani (Sunan Kalijaga: International Journal of Islamic Civilization, 2023)
This article aims to analyze the influence of modern historiography, namely the Annales school and colonial historiography, in the development of Indonesian Islamic historiography. In the traditional period, Indonesian Islamic historiographical themes were only oriented towards political history, the methodology used was not systematic, and the style of writing was descriptive-narrative. This article is a literature study using historical methods consisting of heuristic, verification, interpretation, and historiographical stages. The primary sources used consist of several works of historians influenced by modern historiography. In addition, secondary sources are used in the form of books and scientific articles obtained through direct and digital searches. Furthermore, verification and interpretation of the sources found are carried out and presented in the form of descriptive-analytical articles. This research found that the Annales school and colonial historiography influenced Indonesian Islamic historiography. Its influence lies in the methodological aspects and the spread of global themes. This can be analyzed in the works of Hoesein Djajadiningrat, Sartono Kartodirdjo, and Azyumardi Azra. The education of these historians and the spread of ideas at the beginning of the 20th century became important factors in the internalization of modern historiographical values in Indonesian Islamic historiography. It was concluded that the influence of modern historiography on Indonesian Islamic historiography is the realization of total history writing.